Nitrogen Cycling in Soybean Rhizosphere: Sources and Sinks of Nitrous Oxide (N2O) - Sánchez, Cristina; Minamisawa, Kiwamu (Frontiers in Microbiology, 2019)
Nitrous oxide (N2O) is the third most important greenhouse gas after carbon dioxide and methane, and a prominent ozone-depleting substance. Agricultural soils are the primary anthropogenic source of N2O because of the constant increase in the use of industrial nitrogen (N) fertilizers. The soybean crop is grown on 6% of the world’s arable land, and its production is expected to increase rapidly in the future. In this review, we summarize the current knowledge on N-cycle in the rhizosphere of soybean plants, particularly sources and sinks of N2O. Soybean root nodules are the host of dinitrogen (N2)-fixing bacteria from the genus Bradyrhizobium. Nodule decomposition is the main source of N2O in soybean fields, and both bradyrhizobia and other rhizospheric microorganisms are responsible for the nitrogen transformations that produce N2O. This N2O is either emitted into the atmosphere or further reduced to N2 by the bradyrhizobial N2O reductase (N2OR), encoded by the nos gene cluster. The dominance of nos− indigenous populations of soybean bradyrhizobia results in the emission of N2O into the atmosphere. Hence, inoculation with nos+ or nos++ (mutants with enhanced N2OR activity) bradyrhizobia has proved to be promising strategies to reduce N2O emission in the field. We discussed these strategies, the molecular mechanisms underlying them, and the future perspectives to develop better options for global mitigation of N2O emission from soils.